Exploring Winemaking By-Products of Tinto Cão Grapes: Antioxidant and Antimicrobial Activity against Multiresistant Bacteria - Vanessa Silva; Jessica Ribeiro; Rupesh Kumar Singh; Alfredo Aires; Rosa Carvalho; Virgílio Falco; José Eduardo Pereira; Gilberto Igrejas; Patrícia Poeta (Medical Sciences Forum)
The growing global concern about antimicrobial resistance necessitates alternative strategies against multidrug-resistant bacteria. Our study explores the antimicrobial potential of phenolic compounds from Tinto Cão grape winemaking by-products. These compounds effectively combat S. epidermidis, K. pneumoniae, and L. monocytogenes, showing promise in addressing antimicrobial resistance. Additionally, we found remarkable antioxidant activity in these compounds. Shoot extracts exhibited the strongest antimicrobial performance, while seed and leaf extracts displayed the highest antioxidant capacity. These findings highlight phenolic compounds as a sustainable solution to address multidrug-resistant bacteria, offering an alternative to traditional antibiotics.